Multidecadal dynamics of the Arctic copepod Limnocalanus macrurus in relation to environmental variability in the Baltic Sea. (6th June 2019) - Einberg, Heli; Klais, Riina; Rubene, Gunta; Kornilovs, Georgs; Putnis, Ivars; Ojaveer, Henn
Abstract: The Arctic Limnocalanus macrurus is a prominent representative of large copepods which performs several essential functions in freshwater and marine ecosystems. Being a cold stenotherm species, its distribution is primarily confined to deeper water layers. Based on the long-term observations from one of the largest spatially confined natural populations of this species in the Baltic Sea, we detected profound long-term variability of L. macrurus during 1958–2016: high abundances before the 1980s, then nearly disappearance in the 1990s and recovery in the 2000s. The main environmental parameters explaining the interannual variability of L. macrurus in spring were herring spawning stock biomass in preceding year, winter severity, and bottom water temperature in preceding summer. The effect of winter severity and water temperature was also non-linear. The sliding window correlation analysis pointed to a non-stationary relationship between the abundance of L. macrurus and the key variables. Given the observed pronounced seasonality in the population structure of L. macrurus (young stages dominated in the beginning of the year and only adults were left in the population in summer and autumn) we identified the dynamics of key environmental variables to understand this species under different ecosystem configurations and different combinations of drivers of change.